Cotinine: Beyond that Expected, More than a Biomarker of Tobacco Consumption - Echeverria Moran, Valentina (Frontiers in Pharmacology, 2012)
A greater incidence of tobacco consumption occurs among individuals with psychiatric conditions including post-traumatic stress disorder (PTSD), bipolar disorder, major depression and schizophrenia, compared with the general population. Even when still controversial, it has been postulated that smoking is a form of self-medication that reduces psychiatric symptoms among individuals with these disorders. To better understand the component(s) of tobacco-inducing smoking behavior, greater attention has been directed toward nicotine. However, in recent years, new evidence has shown that cotinine, the main metabolite of nicotine, exhibits beneficial effects over psychiatric symptoms and may therefore promote smoking within this population. Some of the behavioral effects of cotinine compared to nicotine are discussed here. Cotinine, which accumulates in the body as a result of tobacco exposure, crosses the blood-brain barrier and has different pharmacological properties compared with nicotine. Cotinine has a longer plasma half-life than nicotine and showed no addictive or cardiovascular effects in humans. In addition, at the preclinical level, cotinine facilitated the extinction of fear memory and anxiety after fear conditioning, improved working memory in a mouse model of Alzheimer’s disease (AD) and in a monkey model of schizophrenia. Altogether, the new evidence suggests that the pharmacological and behavioral effects of cotinine may play a key role in promoting tobacco smoking in individuals that suffer from psychiatric conditions and represents a new potential therapeutic agent against psychiatric conditions such as AD and PTSD.